Wiley Handbook of Current and Emerging Drug Therapies 2006
DOI: 10.1002/9780470041000.cedt005
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer

Abstract: The etiology and pathophysiology of breast cancer are described, followed by a detailed survey of current and emerging drug therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 152 publications
1
2
0
Order By: Relevance
“…The results also showed that the family history of breast cancer significantly improves the level of knowledge of participants. Similar study findings were reported in the study conducted by Tuyen, D. Q.et al [13] showed that the participants who had history of breast-related diseases had sufficient overall BSE knowledge compared to those who did not.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results also showed that the family history of breast cancer significantly improves the level of knowledge of participants. Similar study findings were reported in the study conducted by Tuyen, D. Q.et al [13] showed that the participants who had history of breast-related diseases had sufficient overall BSE knowledge compared to those who did not.…”
Section: Discussionsupporting
confidence: 89%
“…The first major strategy is to assess breast cancer awareness and knowledge, as well as breast self-examination, among vulnerable women, particularly those in low-income and resource-constrained situations. The second major strategy is to help raise breast selfexamination among vulnerable women, particularly those in low-income and resourceconstrained situations [13].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical Breast Examination (CBE) and Mammography are now the mainstays for early detection of breast cancer [10]. However, these technologies such as mammography screening are too expensive and out of reach of millions of women around the world and in developing countries in particular [11]. As such for many women in poor resourced settings, regular BSE is a critical strategy in early detection of breast cancer and cure, especially in resource limited settings [12, 13] like Ghana.…”
Section: Introductionmentioning
confidence: 99%